(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study was designed to molecular diagnosis of different microorganisms from different soil which polluted by oil. A new Record of Bacillus subtilis, Pseudomonas aeruginosa, Aspergillus flavus, Aspergillus niger, Aspergillus fumigatus were identified respectively, based on 16S rDNA and 18S rDNA sequencing fingerprinting data. Also, some gene have detected like Bacillus subtilis strain RPL7 16S ribosomal RNA gene, Pseudomonas putida strain Xuyi_351_2 16S ribosomal RNA gene, Aspergillus flavus clone SF_652 small subunit ribosomal RNA gene, Aspergillus flavus clone SF_652 small subunit ribosomal RNA gene, Aspergillus niger isolate SUMS0061 18S ribosomal RNA gene, Aspergillus niger isolate SUMS0061 18S ribosomal RNA gene, Aspergillus fumigatus isolate AUMC13622 small subunit ribosomal RNA gene The presence of bacteria and fungi in the study's polluted soils shows that microorganisms are ubiquitous, diverse, and capable of adapting to severe situations. When comparing oil-polluted soils to unpolluted soils, the characterization methods revealed a considerable decrease in microbial population, composition, and diversity.